THE MAPPING OF KEI LANGUAGE TEACHING MATERIALS AND PRESENTATION AT SENIOR HIGH SCHOOLS IN KEI ISLANDS, SOUTHEAST MALUKU - Akihary, Wilma; Rahajaan, Sopiah (TALENTA, 2021)
This study aimed to map Kei language teaching materials' content and how to present them in Senior High Schools in the Kei Islands, Southeast Maluku. The approach in this study was descriptive qualitative by using a purposive sampling technique. The data were in the form of oral and written. They were collected through in-depth interviews and participant observation. The validity of the data was tested using the triangulation of data sources. Furthermore, the data were analyzed using Miles and Huberman's analysis, which consisted of three stages: data reduction, data presentation, and conclusion drawing. The results showed that only two Senior High Schools of 45 schools in Kotamadya Tual and Southeast Maluku Regency taught Kei language as local content in Senior High Schools. The teaching materials found varied, namely the Kei language and culture packaged on school initiatives. The other was Kei literature for elementary schools published by the Southeast Maluku Regency Education and Culture Office in 2004. Besides, Kei language teaching did not have a presentation of teaching materials structured. The absence of representative teaching materials and unstructured presentation of teaching materials impacts the implementation of Kei language teaching in the field. This needs to be addressed by related agencies and education observers. A solution that can be done is that it is necessary to provide legal/statutory powers to teach Kei from the local government. The Education Office needs to form a group to develop Kei language teaching materials for Senior High Schools to revitalize the Kei language in the world of education.